Fundamental limits on the losses of phase and amplitude optical actuators. Issue 6 (21st September 2015) - Zanotto, Simone; Morichetti, Francesco; Melloni, Andrea
Abstract : Amplitude and phase are the basic properties of all wave phenomena; as far as optical waves are concerned, the ability to act on these variables is at the root of a wealth of switching devices. To quantify the performance of an optical switching device, an essential aspect is to determine the tradeoff between the insertion loss and the amplitude or phase modulation depth. Here it is shown that every optical switching device is subject to such a tradeoff, intrinsically connected to the dielectric response of the materials employed inside the switching element itself. This limit finds its roots in fundamental physics, as it directly derives from Maxwell's equations for linear dielectrics, and is hence applicable to a wide class of optical components. Furthermore, a result is that concepts such as filtering, resonance, and critical coupling could be of advantage in approaching the limit. Abstract: Amplitude and phase are the basic properties of all wave phenomena; as far as optical waves are concerned, the ability to act on these variables is at the root of a wealth of switching devices. To quantify the performance of an optical switching device, an essential aspect is to determine the tradeoff between the insertion loss and the amplitude or phase modulation depth. Here it is shown that every optical switching device is subject to such a tradeoff, intrinsically connected to the dielectric response of the materials employed inside the switching element itself. This limit finds its roots in fundamental physics, as it directly derives from Maxwell's equations for linear dielectrics, and is hence applicable to a wide class of optical components. Furthermore, a result is that concepts such as filtering, resonance, and critical coupling could be of advantage in approaching the limit.